Exploring the Potential of Halloumi Second Cheese Whey for the Production of Lactic Acid Cultures for the Dairy Industry - Naziri, Eleni; Papadaki, Eugenia; Savvidis, Iordanis; Botsaris, George; Gkatzionis, Konstantinos; Mugampoza, Ediriisa; Mantzouridou, Fani Th. (My University, 2023)
Production of halloumi cheese in Cyprus has increased rapidly over the last decade since the popularity of the cheese is growing. This results in excess production of whey streams that pose serious environmental concerns and are difficult to manage. In our study, the poorly investigated second cheese whey (SCW) generated after the extraction of anari, a by-product of halloumi cheese manufacture, was examined for dairy industry lactic acid bacteria (LAB) culture production. The LAB studied were all initially isolated from SCW. These LAB were molecularly identified and characterized in an attempt to explore their potential use as starter cultures for the dairy industry. A total of 11 Gram-positive and catalase-negative isolates were identified, belonging to four different species/subspecies: Lactobacillus delbrueckii subsp. lactis, Lactobacillus delbrueckii subsp. jakobsenii, Lactobacillus leichmannii and Lactobacillus crispatus. Lactose/galactose utilization tests demonstrated species-specific differences in galactose and lactose catabolism. Interestingly, culturing the selected isolates in SCW supplemented with skimmed milk (30% total solids) improved their freeze-drying tolerance (75–91% survival rate depending on the species). Moreover, isolates in vacuum-packed powders maintained viability and metabolic activity over 3-month storage at 4 °C.
Keywords: 16S rRNA gene sequencing; freeze-drying; galactose catabolism; halloumi cheese; lactic acid bacteria; lactose catabolism; second cheese whey; storage